Self-repairing resin composition and self-repairing film structure
The self-healing resin composition, synthesized from specific monomers, addresses the lack of transparency and adjustability in existing self-healing materials by forming a repairable and transparent membrane layer on surfaces, effectively addressing the limitations of current self-healing technologies.
Patent Information
- Application Number
- CN202311218187.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-14
AI Technical Summary
Existing self-healing materials for surfaces lack high transparency and adjustable haze or gloss features, and current methods to adjust haze often compromise the material's properties or lead to issues like particle dropout.
A self-healing resin composition and membrane structure are developed, comprising 20-50 weight percent self-healing resin, 1-10 weight percent hardener, 0.1-3 weight percent haze agent, and 40-80 weight percent solvent, with the resin synthesized from polyether polyol, diisocyanate monomer, and phenol monomer, having a hydroxyl to isocyanate molar ratio of 1.33-2.0 and number average molecular weight of 30,000-200,000, allowing for adjustable transparency and haze control without compromising self-healing functionality.
The self-healing resin composition forms a transparent membrane layer that can self-repair scratches at low temperatures or room temperature, maintaining self-healing functionality even with haze agents, and is suitable for applications on polyurethane or PVC surfaces, effectively extending the lifespan of materials by restoring their original state.
Smart Images

Figure CN119613664A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a self-repairing resin composition and a self-repairing film structure, and in particular to a self-repairing resin composition and a self-repairing film structure with high transparency and adjustable haze. Background Art
[0002] Currently, many substrates on the market have insufficient scratch resistance, such as car shells, mobile phone shells or laptop shells. During use, permanent scratches are easily formed, affecting the appearance. In order to extend the service life, a protective layer is generally attached to the surface of the substrate to maintain the appearance.
[0003] With the advancement of technology and the discovery of self-healing materials, the industry has begun to apply self-healing materials to substrates to form a protective layer on the surface of the substrate. In this way, when the substrate is scratched by external forces, the surface of the substrate can be restored to its previous appearance by heating. However, existing self-healing materials cannot have the characteristics of high transparency and adjustable matte or glossy gloss at the same time.
[0004] For example, in order to adjust the matte properties of the protective layer, the prior art provides a method of performing a matte treatment on the self-repairing material and adding scattering particles to the self-repairing material. However, the matte treatment will destroy the properties of the self-repairing material itself, and adding scattering particles will easily cause the problem of scattering particles falling off. Therefore, how to formulate a self-repairing resin composition through the design and improvement of the components has become one of the important issues that this business wants to solve. Summary of the invention
[0005] The technical problem to be solved by the present application is to provide a self-repairing resin composition and a self-repairing membrane structure in view of the deficiencies of the prior art.
[0006] In order to solve the above technical problems, one of the technical solutions adopted in this application is to provide a self-healing resin composition. The self-healing resin composition includes: 20 to 50 parts by weight of self-healing resin, 1 to 10 parts by weight of hardener, 0.1 to 3 parts by weight of matte agent and 40 to 80 parts by weight of solvent. The self-healing resin is synthesized from polyester polyol, diisocyanate monomer and bisphenol monomer. The molar ratio of hydroxyl group to cyanate group in the monomer of the synthetic self-healing resin is 1.33 to 2.0, and the number average molecular weight of the self-healing resin is 30,000 g / mol to 200,000 g / mol.
[0007] Furthermore, the total weight of monomers for synthesizing the self-healing resin is 100 weight percent, the content of polyester polyol is 75 weight percent to 90 weight percent, the content of diisocyanate monomer is 3 weight percent to 10 weight percent, and the content of bisphenol monomer is 5 weight percent to 15 weight percent.
[0008] Furthermore, the number average molecular weight of the polyester polyol is 3000 g / mol to 5000 g / mol.
[0009] Furthermore, the polyester polyol is synthesized from adipic acid, 1,4-butanediol, 1,6-hexanediol and 2-methyl-1,3-propanediol.
[0010] Furthermore, the molar ratio of 1,4-butanediol to 1,6-hexanediol is 1:0.5-2, and the molar ratio of 1,4-butanediol to 2-methyl-1,3-propanediol is 1:0.33-3.
[0011] Furthermore, the diisocyanate monomer is selected from the group consisting of hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, methylene diphenyl diisocyanate and hexamethylene diisocyanate.
[0012] Furthermore, the bisphenol monomer is selected from the group consisting of bisphenol A, bis(4-hydroxyphenyl)cyclohexane, 1,1′-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 9,9-bis-[(4-hydroxyethoxy)phenyl]fluorene and dimethylbisphenol A.
[0013] In order to solve the above technical problems, another technical solution adopted by the present application is to provide a self-repairing film structure. The self-repairing film structure includes a substrate layer, a self-repairing film layer, an adhesive layer and a release layer. The substrate layer has a first surface and a second surface. The self-repairing film layer is formed on the first surface, and the self-repairing film layer is formed by the aforementioned self-repairing resin composition. The adhesive layer is arranged on the second surface. The release layer is arranged on the adhesive layer so that the adhesive layer is arranged between the substrate layer and the release layer.
[0014] Furthermore, the material of the substrate layer is polyurethane or polyvinyl chloride.
[0015] Furthermore, the thickness of the self-healing film layer is 5 microns to 50 microns.
[0016] One of the beneficial effects of the present application is that the self-healing resin composition and self-healing membrane structure provided by the present application can achieve the self-healing function of the self-healing film layer formed by the self-healing resin composition under short-term heating or at room temperature through the technical scheme of "the self-healing resin is synthesized from polyester polyol, diisocyanate monomer and bisphenol monomer", "the molar ratio of hydroxyl group to cyanate group in the monomer for synthesizing the self-healing resin is 1.33 to 2.0" and "the number average molecular weight of the self-healing resin is 30,000 g / mol to 200,000 g / mol".
[0017] To further understand the features and technical contents of the present application, please refer to the following detailed description and drawings of the present application. However, the drawings provided are only for reference and illustration and are not intended to limit the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a side view schematic diagram of the self-repairing membrane structure of the present application. DETAILED DESCRIPTION
[0019] The following is an explanation of the implementation methods of the "self-healing resin composition and self-healing membrane structure" disclosed in the present application through specific examples. Those skilled in the art can understand the advantages and effects of the present application from the contents disclosed in this specification. The present application can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the concept of the present application. In addition, the drawings of the present application are only simple schematic illustrations and are not depicted in actual size. It is stated in advance. The following implementation methods will further explain the relevant technical content of the present application in detail, but the disclosed content is not intended to limit the scope of protection of the present application. In addition, the term "or" used in this article may include any one or more combinations of the associated listed items depending on the actual situation.
[0020] The present application provides a self-repairing resin composition, which has a lower chemical bond energy and can be self-repaired at a lower temperature. The self-repairing resin composition of the present application has high transparency and can maintain the self-repairing function even if frosting agent particles are added. The self-repairing resin composition can be coated on a substrate and can form a self-repairing material after curing to achieve a protective effect.
[0021] In addition, for the convenience of use, the present application also provides a self-repairing membrane structure made of a self-repairing resin composition. The self-repairing membrane structure can be attached to the surface to be protected. The self-repairing membrane structure itself has a self-repairing function, which can help the material return to its original state. Once the self-repairing membrane structure is cracked or deformed due to external force, if it can be properly heated, the material can return to its original state through thermal expansion (physical repair), or the originally broken bond parts can be re-contacted and bonded due to thermal expansion (chemical repair).
[0022] In the present application, the self-healing material can achieve the effect of repairing cracks through the interaction between molecules by briefly heating at a temperature of 80° C. to 130° C. or at room temperature (eg, 50° C.).
[0023] It is worth noting that the self-healing resin composition of the present application is particularly suitable for coating on a substrate of a polyurethane material or a polyvinyl chloride material, so that a self-healing film layer (self-healing material) is formed on the surface of the substrate, thereby achieving the effect of protecting the substrate.
[0024] The present application can make the self-repairing material have the function of self-repairing by selecting monomers, designing monomer structures and adjusting the content of monomers. In addition, the self-repairing resin composition of the present application can be used to form a self-repairing film layer with high transparency, and its surface can also be adjusted to be matte or glossy.
[0025] Taking the total weight of the self-healing resin composition as 100 parts by weight, the self-healing resin composition of the present application includes: 20 to 50 parts by weight of self-healing resin, 1 to 10 parts by weight of hardener, 0.1 to 3 parts by weight of matte agent and 40 to 80 parts by weight of solvent.
[0026] In the present application, the self-healing resin is synthesized from polyester polyol, diisocyanate monomer and bisphenol monomer. Through the selection of different monomers, the design of monomer structure and the adjustment of monomer content, the self-healing resin composition (self-healing material) can have more hydrogen bonds after curing. Once cracks or deformations are generated by external forces, the self-healing material can return to its original shape at an appropriate temperature.
[0027] In an exemplary embodiment, the total weight of monomers for synthesizing the self-healing resin is 100 weight percent, the content of polyester polyol is 75 weight percent to 90 weight percent, the content of diisocyanate monomer is 3 weight percent to 10 weight percent, and the content of bisphenol monomer is 5 weight percent to 15 weight percent.
[0028] Preferably, the content of the polyester polyol is 85 weight percent to 90 weight percent, the content of the diisocyanate monomer is 3 weight percent to 5 weight percent, and the content of the bisphenol monomer is 5 weight percent to 10 weight percent.
[0029] Moreover, in the present application, the number average molecular weight of the self-healing resin is 30000 g / mol to 200000 g / mol. When the number average molecular weight of the self-healing resin exceeds the above range, the repair effect cannot be achieved. For example, the number average molecular weight of the self-healing resin can be 40000 g / mol, 50000 g / mol, 60000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol, 100000 g / mol, 110000 g / mol, 120000 g / mol, 130000 g / mol, 140000 g / mol 150000 g / mol, 160000 g / mol, 170000 g / mol, 180000 g / mol or 190000 g / mol.
[0030] In all monomers used to synthesize the self-healing resin, the functional group ratio of hydroxyl to cyanate is also an important parameter. In the present application, the functional group ratio of hydroxyl to cyanate in the monomers used to synthesize the self-healing resin is 1.33 to 2.0. For example, the functional group ratio of hydroxyl to cyanate in the monomers used to synthesize the self-healing resin can be 1.35, 1.40, 1.45, 1.50, 1.55, 1.6, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90 or 1.95.
[0031] That is to say, the content of hydroxyl groups in the monomers for synthesizing the self-healing resin is greater than the content of cyanate groups. After the polyester polyol, diisocyanate monomer and bisphenol monomer are polymerized, the self-healing resin can still retain an appropriate content of hydroxyl groups in order to form hydrogen bonds and achieve a self-healing effect.
[0032] Polyester polyols are synthesized from diol monomers and diacid monomers. The diol monomers include 1,4-butanediol, 1,6-hexanediol and 2-methyl-1,3-propanediol, and the diacid monomers include adipic acid. When 1,4-butanediol, 1,6-hexanediol and 2-methyl-1,3-propanediol are selected and combined with adipic acid, the polyester polyols of the present application can have the best molecular distance and sufficient hydroxyl groups compared to other monomers, thereby balancing and obtaining the best repair properties.
[0033] In an exemplary embodiment, the total weight of monomers for synthesizing polyester polyol is 100 weight percent, the content of 1,4-butanediol is 30 weight percent to 40 weight percent, the content of 1,6-hexanediol is 20 weight percent to 30 weight percent, the content of 2-methyl-1,3-propanediol is 15 weight percent to 20 weight percent, and the content of adipic acid is 20 weight percent to 40 weight percent.
[0034] Specifically, in the diol monomers for synthesizing the polyester polyol, the molar ratio of 1,4-butanediol to 1,6-hexanediol is 1:0.5 to 2, and the molar ratio of 1,4-butanediol to 2-methyl-1,3-propanediol is 1:0.33 to 3. Therefore, the polyester polyol can have ideal characteristics.
[0035] It is worth noting that the present application first uses diol monomers and diacid monomers to polymerize polyester polyols, and then polymerizes the polyester polyols with diisocyanate monomers and bisphenol monomers. It is not to mix all the monomers (diol monomers and diacid monomers) for synthesizing polyester polyols with diisocyanate monomers and bisphenol monomers for polymerization reaction. In this way, the properties of polyester polyols can be precisely controlled to ensure that the final self-healing resin has an ideal self-healing effect.
[0036] The diisocyanate monomer may be selected from the group consisting of hexamethylene diisocyanate (HDI), 4,4′-diisocyanatodicyclohexylmethane (H12MDI), isophorone diisocyanate (IPDI), methylene diphenyl diisocyanate (MDI) and hexamethylene diisocyanate trimer (HDI-trimer).
[0037] The bisphenol monomer may be selected from the group consisting of bisphenol A (BPA), bis(4-hydroxyphenyl)cyclohexane (BPZ), 1,1'-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (BP-TMC), bisphenoxyethanolfluorene (BP-EF) and dimethyl-bisphenol A (DMBPA).
[0038] According to the above content, the self-healing resin can be represented by formula (I).
[0039]
[0040] In formula (I), "X" represents a structure formed by polymerization of polyester polyol, "Y" represents a structure formed by polymerization of diisocyanate monomer, and "Z" represents a structure formed by polymerization of bisphenol monomer. The number average molecular weight of the polyester polyol may be 3000 g / mol to 5000 g / mol. However, the present application is not limited thereto.
[0041] In an exemplary embodiment, hexamethylene diisocyanate can be selected as the diisocyanate monomer, and bisphenol A can be selected as the bisphenol monomer. The self-healing resin synthesized from polyester polyol, hexamethylene diisocyanate and bisphenol A can be represented by formula (II).
[0042]
[0043] In formula (II), "X" represents a structure formed by polymerization of polyester polyol. The number average molecular weight of the self-healing resin may be 30,000 g / mol to 200,000 g / mol. However, the present application is not limited thereto.
[0044] In the self-healing resin composition, the hardener may be selected from the group consisting of hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, methylene diphenyl diisocyanate and hexamethylene diisocyanate.
[0045] In the self-repairing resin composition, the matte agent may be selected from the group consisting of polymethyl methacrylate particles, polystyrene particles and silicon dioxide particles. The particle size of the matte agent is 0.5 micrometers to 10 micrometers.
[0046] Since this case uses specific monomers to synthesize the self-healing resin, even if a matte agent is added in the future, it will not negatively affect the self-healing effect of the self-healing resin.
[0047] In the self-healing resin composition, the solvent may be selected from the group consisting of ethyl acetate, acetone, propylene glycol methyl ether acetate, dimethylacetamide, butanone, isopropanol and ethanol. Preferably, the solvent may be dimethylacetamide. After considering the processability, the solid content of the self-healing resin composition may be 35% to 45%.
[0048] In addition to the above components, the self-repairing resin composition may further include an ultraviolet absorber, a leveling agent, a defoaming agent, a catalyst or a combination thereof.
[0049] For example, the catalyst may be, but is not limited to, stannous octoate, dibutyltin dilaurate, dimethyl methylphosphonate, or diethyl ethylphosphonate. Moreover, the addition of the catalyst may help the synthesis of the self-healing resin and the repair of the self-healing resin. With the total weight of the self-healing resin composition being 100 parts by weight, the amount of the catalyst added may be 1 part by weight to 5 parts by weight.
[0050] See also Figure 1 As shown, the self-repairing film structure of the present application includes: a substrate layer 1 , a self-repairing film layer 2 , an adhesive layer 3 and a release layer 4 .
[0051] The substrate layer 1 has a first surface 11 and a second surface 12 .
[0052] After the self-repairing resin composition is coated on the first surface 11 of the substrate layer 1, after drying and curing steps, the self-repairing film layer 2 can be formed on the first surface 11. In other words, the self-repairing film layer 2 is formed by curing the self-repairing resin composition.
[0053] The adhesive layer 3 is disposed on the second surface 12 of the substrate layer 1 .
[0054] The release layer 4 is disposed on the adhesive layer 3 so that the adhesive layer 3 is disposed between the substrate layer 1 and the release layer 4. In addition, the peeling strength between the release layer 4 and the adhesive layer 3 is relatively low, so the release layer 4 can be torn off before use, and then the substrate layer 1 and the self-healing film layer 2 can be disposed on the plane to be protected through the adhesive layer 3.
[0055] The self-repairing film structure of the present application is flexible, and after the release layer 4 is torn off, it can be attached to any surface through the adhesive layer 3 to achieve the effect of protecting the surface.
[0056] To facilitate the description of the function of the self-healing resin composition of the present application, polyester polyol is prepared according to the following method, and the self-healing resin is synthesized using polyester polyol, isocyanate monomer and bisphenol monomer. However, the following examples are only for the convenience of description, and the present application is not limited thereto.
[0057] [Synthesis of polyester polyols]
[0058] 50 g of 1,4-butanediol, 60 g of 1,6-hexanediol, 60 g of 2-methyl-1,3-propanediol and 190 g of adipic acid were mixed and reacted at a temperature of 150° C. to 200° C. for 1 to 2 hours to obtain a polyester polyol. In this example, the number average molecular weight of the polyester polyol is 4000 g / mol.
[0059] [Synthesis of self-healing resin]
[0060] According to the equivalent ratios in Tables 1 and 2, polyester polyol and hexamethylene diisocyanate (diisocyanate monomer) were mixed and reacted at 80°C for 1 to 2 hours, and then bisphenol A (bisphenol monomer) and dibutyltin dilaurate (catalyst) were added and reacted at 100°C for 5 to 6 hours to obtain the added self-healing resins in Examples 1 to 5 and Comparative Examples 1 to 4, respectively.
[0061] In order to test the repair effect of the self-repairing film layer, 100 parts by weight of self-repairing resin, 10 parts by weight of hardener, 0.5 parts by weight of matte agent and 300 parts by weight of solvent were mixed and formulated into self-repairing resin compositions of Examples 1 to 5 and Comparative Examples 1 to 4.
[0062] When the solid content of the self-healing resin composition is 40%, the viscosity of the self-healing resin composition may be 500 cps to 10000 cps, for example, 1000 cps, 2000 cps, 3000 cps, 4000 cps, 5000 cps, 6000 cps, 7000 cps, 8000 cps or 9000 cps. However, the present application is not limited thereto.
[0063] After the self-repairing resin composition is prepared, the self-repairing resin composition is coated on a substrate layer of polyurethane material or polyvinyl chloride, baked at a temperature of 80°C to 120°C for 3 to 5 minutes, then aged at a temperature of 40°C to 70°C, and stored for 24 to 120 hours, so as to form a self-repairing film layer with a thickness of 5 to 50 microns on the substrate layer, and obtain a sample to be tested.
[0064] In the test experiment of the repair time, a copper brush is used to form scratches on the surface of the test sample, and then the scratched test sample is placed in an environment of 100°C to observe the time required for the surface of the test sample to return to its original state, so as to evaluate the scratch repair effect of the test sample. The results are listed in Table 1.
[0065] Table 1
[0066]
[0067]
[0068] Table 2
[0069]
[0070] From the contents of Table 1 and Table 2, it can be seen that the self-repairing resin composition of the present application can form a self-repairing film layer with self-repairing function. By briefly heating at a temperature of 80°C to 130°C, the cracks can be repaired through the interaction between molecules.
[0071] It can be seen from the contents of Table 1 and Table 2 that the ratio of functional groups in the synthetic self-healing resin monomer will affect the repair effect of the self-healing resin. According to the results of Example 1 and Comparative Example 1, when the functional group ratio of hydroxyl group to cyanate group in the self-healing resin (OH / NCO functional group ratio) is less than 1.33, the self-healing film layer cannot have a self-healing effect. According to the results of Example 2 and Comparative Example 2, when the functional group ratio of hydroxyl group to cyanate group in the self-healing resin is greater than 2.5, the self-healing film layer cannot have a self-healing effect. Therefore, the functional group ratio of hydroxyl group to cyanate group in the self-healing resin needs to be 1.33 to 2.0, preferably 1.33 to 1.66.
[0072] It can be seen from the contents of Table 1 and Table 2 that the molecular weight of the self-healing resin will also affect the repair effect of the self-healing resin. According to the results of Comparative Example 3, when the molecular weight of the self-healing resin is less than 30,000 g / mol, the self-healing film layer cannot have a self-healing effect. According to the results of Example 5 and Comparative Example 4, when the molecular weight of the self-healing resin is greater than 200,000 g / mol, the self-healing film layer cannot have a self-healing effect. Therefore, the number average molecular weight of the self-healing resin needs to be 30,000 g / mol to 200,000 g / mol. Preferably, the number average molecular weight of the self-healing resin is 50,000 g / mol to 150,000 g / mol.
[0073] [Beneficial Effects of Embodiments]
[0074] One of the beneficial effects of the present application is that the self-healing resin composition and self-healing membrane structure provided by the present application can achieve the self-healing function of the self-healing film layer formed by the self-healing resin composition under short-term heating or at room temperature through the technical scheme of "the self-healing resin is synthesized from polyester polyol, diisocyanate monomer and bisphenol monomer", "the molar ratio of hydroxyl group to cyanate group in the monomer for synthesizing the self-healing resin is 1.33 to 2.0" and "the number average molecular weight of the self-healing resin is 30,000 g / mol to 200,000 g / mol".
[0075] Furthermore, in order to enhance the self-healing effect of the self-healing resin composition, the present application controls the monomer type and content of the synthesized self-healing resin, selects specific types of polyester polyols, diisocyanate monomers and bisphenol monomers to enhance the self-healing effect of the self-healing film layer. In addition, the present application further adjusts the monomer type and ratio of the synthesized polyester polyol and the molecular weight of the polyester polyol to control the properties of the polyester polyol.
[0076] The contents disclosed above are only preferred feasible embodiments of the present application, and are not intended to limit the protection scope of the claims of the present application. Therefore, all equivalent technical changes made using the contents of the present application specification and drawings are included in the protection scope of the claims of the present application.
Claims
1. A self-repairing resin composition, characterized in that: The self-repairing resin composition comprises: 20 to 50 parts by weight of a self-healing resin, wherein the self-healing resin is synthesized from a polyester polyol, a diisocyanate monomer and a bisphenol monomer, wherein the molar ratio of hydroxyl groups to cyanate groups in the monomers synthesizing the self-healing resin is 1.33 to 2.0, and the number average molecular weight of the self-healing resin is 30,000 to 200,000 g / mol; 1 to 10 parts by weight of a hardener; 0.1 to 3 parts by weight of a matte agent; and 40 to 80 parts by weight of solvent.
2. The self-healing resin composition according to claim 1, characterized in that: Taking the total weight of monomers for synthesizing the self-healing resin as 100 weight percent, the content of the polyester polyol is 75 weight percent to 90 weight percent, the content of the diisocyanate monomer is 3 weight percent to 10 weight percent, and the content of the bisphenol monomer is 5 weight percent to 15 weight percent.
3. The self-healing resin composition according to claim 1, characterized in that: The number average molecular weight of the polyester polyol is 3000 g / mol to 5000 g / mol.
4. The self-healing resin composition according to claim 1, characterized in that: The polyester polyol is synthesized from adipic acid, 1,4-butanediol, 1,6-hexanediol and 2-methyl-1,3-propanediol.
5. The self-repairing resin composition according to claim 4, characterized in that: The molar ratio of 1,4-butanediol to 1,6-hexanediol is 1:0.5 to 2, and the molar ratio of 1,4-butanediol to 2-methyl-1,3-propanediol is 1:0.33 to 3.
6. The self-healing resin composition according to claim 1, characterized in that: The diisocyanate monomer is selected from the group consisting of hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, methylene diphenyl diisocyanate and hexamethylene diisocyanate.
7. The self-healing resin composition according to claim 1, characterized in that: The bisphenol monomer is selected from the group consisting of bisphenol A, bis(4-hydroxyphenyl)cyclohexane, 1,1'-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 9,9-bis-[(4-hydroxyethoxy)phenyl]fluorene and dimethylbisphenol A.
8. A self-repairing membrane structure, characterized in that: The self-repairing membrane structure comprises: A substrate layer having a first surface and a second surface; a self-repairing film layer formed on the first surface, wherein the self-repairing film layer is formed by the self-repairing resin composition according to any one of claims 1 to 7; an adhesive layer disposed on the second surface; and A release layer is disposed on the adhesive layer so that the adhesive layer is disposed between the substrate layer and the release layer.
9. The self-repairing membrane structure according to claim 8, characterized in that: The material of the substrate layer is polyurethane or polyvinyl chloride.
10. The self-repairing membrane structure according to claim 8, characterized in that: The thickness of the self-repairing film layer is 5 microns to 50 microns.